2021
DOI: 10.3390/jcm10214967
|View full text |Cite|
|
Sign up to set email alerts
|

Six-Month Results on Treatment Adherence, Physical Activity, Spinal Appearance, Spinal Deformity, and Quality of Life in an Ongoing Randomised Trial on Conservative Treatment for Adolescent Idiopathic Scoliosis (CONTRAIS)

Abstract: Adolescents with idiopathic scoliosis (AIS) often receive conservative treatments aiming to prevent progression of the spinal deformity during puberty. This study aimed to explore patient adherence and secondary outcomes during the first 6 months in an ongoing randomised controlled trial of three treatment interventions. Interventions consisted of physical activity combined with either hypercorrective Boston brace night shift (NB), scoliosis-specific exercise (SSE), or physical activity alone (PA). Measures at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…In addition, it is expected to be able to deviate from the target of surgical treatment by improving the distorted appearance change in patients with a Cobb angle of 25° or more. CONTRAIS may help adolescents with scoliosis have a low quality of life and reduced self-esteem, and also when physicians consider more aggressive treatment ( Dufvenberg et al, 2021 ). In the case of surgical treatment for AIS, there is a problem that postoperative pain is large in young patients, and most patients visit a hospital for pain treatment because the postoperative pain does not resolve ( Kwan et al, 2020 ; Lee et al, 2020 ; Roye et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is expected to be able to deviate from the target of surgical treatment by improving the distorted appearance change in patients with a Cobb angle of 25° or more. CONTRAIS may help adolescents with scoliosis have a low quality of life and reduced self-esteem, and also when physicians consider more aggressive treatment ( Dufvenberg et al, 2021 ). In the case of surgical treatment for AIS, there is a problem that postoperative pain is large in young patients, and most patients visit a hospital for pain treatment because the postoperative pain does not resolve ( Kwan et al, 2020 ; Lee et al, 2020 ; Roye et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, nonsurgical interventions for AIS are controversial ( Day et al, 2019 ; Fan et al, 2020 ). Previous studies have suggested that nonsurgical therapy is an effective treatment for scoliosis, particularly AIS ( Dufvenberg et al, 2021 ; Ng et al, 2017 ). However, the prevalence of scoliosis is increasing, and many researchers argue that current treatments for AIS are insufficient ( Cheung et al, 2020 ; Płaszewski and Bettany-Saltikov, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported treatment adherence, motivation to carry out treatment, and capability to perform treatment were also collected using a similar scale. These data were collected at each 6-month follow-up …”
Section: Methodsmentioning
confidence: 99%
“…Detailed information 12 about the interventions is provided in the appendices of the published protocol 10 and 6-month interim patient-reported outcomes. 13 Patients in the NB group received a custom-designed, hypercorrective Boston scoliosis night brace (Camp Scandinavia AB). 14 The brace was prescribed to be worn for 8 hours during the night.…”
Section: Methodsmentioning
confidence: 99%
“…A range of treatments for AIS are available and these range from exercises to bracing and finally surgery for those with severe disease and a large degree of deviation (i.e., Cobb angle) ( Day et al, 2019 ; Kaelin, 2020 ; Dufvenberg et al, 2021 ; Bowden et al, 2022 ; Park et al, 2022 ; Seleviciene et al, 2022 ; Turner et al, 2022 ; Zaina et al, 2022 ). For those patients with severe disease and needing surgery, the implantation of rods and screws can alleviate the curvature-associated complications but can also affect quality of life during post-skeletal maturity.…”
Section: Sex Differences In Risk For Injury To Msk Tissues During Dev...mentioning
confidence: 99%